A putative AGO protein, OsAGO17, positively regulates grain size and grain weight through OsmiR397b in rice. Issue 4 (7th October 2019) - Zhong, Jun; He, Weijie; Peng, Zhu; Zhang, Hui; Li, Feng; Yao, Jialing
Summary: Argonaute (AGO) proteins and small RNAs (sRNAs) are core components of the RNA‐induced silencing complex (RISC). It has been reported that miRNAs regulate plant height and grain size in rice, but which AGO is involved in grain size regulation remains unclear. Here, we report that enhanced expression of OsAGO17, a putative AGO protein, could improve grain size and weight and promote stem development in rice. Cytological evidence showed that these effects are mainly caused by alteration of cell elongation. Expression analyses showed that OsAGO17 was highly expressed in young panicles and nodes, which was consistent with the expression pattern of OsmiR397b. SRNA sequencing, stem‐loop RT‐PCR and sRNA blotting showed that the expression of OsmiR397b was reduced in ago17 and enhanced in the OsAGO17 OE lines. Four OsmiR397b target laccase ( LAC ) genes showed complementary expression patterns with OsAGO17 and OsmiR397b. Combined with the results of immunoprecipitation (IP) analysis, we suggested that OsAGO17 formed an RISC with OsmiR397b and affected rice development by suppression of LAC expression. In conclusion, OsAGO17 might be a critical protein in the sRNA pathway and positively regulates grain size and weight in rice.